National Union of Railwaymen sash, 1925 (1925)
1925 1918-1939 "National Union of Railwaymen sash, 1925" [T0532.jpg], 1925 Part of the NUR Rugby Branch union regalia and worn by the Branch Secretary on demonstrations and official occasions.